State of local immunity in patients with chronic apical periodontitis (LLC "Endo Press", 2020)
The aim of this study was to determine the status of local immunity in the oral cavity of patients with chronic apical periodontitis before and after management of endodontic treatment. To assess the state of local immunity studied the content of secretory immunoglobulin A (sIgA), serum IgA and IgG by radial immunodiffusion. The coefficient of the balance factor of local immune factors (CBF) was calculated as an integrated indicator of the local immunity of the oral cavity. As a result of research of local immunity of oral cavity for 42 patients in age 35-44 with a diagnosis chronic apical periodontitis is educed decline of level of secretory immunoglobuline A and lizocyme, reduction of balanced factor of the local immunity balance coefficient. Rational endodontic treatment, oral cavity sanation, educating to the rational hygiene of the oral cavity is accompanied by the positive dynamics of the immunological indexes.